A Case Study: Kolej YPM Kuala Lumpur - Mamat, Saburiah (1997)

(untitled)
Human Resource problems have becoming severe at YPM in general and at Kolej YPM Kuala Lumpur in specific.The problems could be costly if corrective measures are not taken at the early stage as people keep coming and going. This case study is meant to analyse the internal problem of the College which were due to the miss-communication, lack of managerial skill among the managers and the strategic planning of the college. Because of that, people who were not happy left the college even after having giving service for 3-5 years. Why can't they be loyal to the college and stay for their life time? Using the issue of turnover and satisfaction among the employees, the recommendation given to solve the problem were: Improve the communication process and enhance the managerial skill among the managers.